CURRENT STATUS OF URBAN DRAINAGE SYSTEM AND ITS PROBLEM IN NETROKONA MUNICIPAL, DHAKA (Journal of Institute of Science and Technology, 2017)
Rapid and haphazard urbanization has triggered environmental hazards in Bangladesh. Analogously, Netrokona Municipal is also facing problems due to unplanned and unstable urban infrastructural development. The quest of the study was to explore the status of current urban drainage system and its problem. Therefore, a preliminary reconnaissance survey was accomplished in the study area and then a semi-structured questionnaire was designed. By adopting simple random sampling method, the study area was surveyed covering 50 respondents in different wards to collect primary data. Results revealed that poor drainage system (PDS) is one of the most liable factors for environmental deterioration. The maximum urban drainage system was found unclosed with number of 49 (i.e., 98%). It was 34 drains were made of brick, while 17 were worst type, 32 had odor problem, 20 were not well designed, 29 had inadequacy of drains,18 with poor technical fitness, 22 wastes disposal in gutters,18 had clogging of ditches & drains, and 15 with broken road surface respectively. The consequent major environmental and health problems were flash-flooding (42%), and skin disease (38%) respectively. In case of public opinion, the highest percentage (i.e., 30%) suggested to stoutly prohibit dumping of garbage into gutters. PDS was found strongly positive correlated with its effects on environment (r=0.98) and on public health (r=0.91). Thereby, present PDS affects the environment as-well-as public health by enhancing frequent flash-floods and spreading diseases within the study area.Journal of Institute of Science and TechnologyVolume 22, Issue 1, July 2017, Page: 165-178